Analisis Pengelolaan Administrasi Keuangan pada Industri Batik di Kampoeng Batik Laweyan Kota Surakarta - Bagus Widhi Hantoro; Susantiningrum Susantiningrum; Jumiyanto Widodo (Politeknik Kampar, 2023)
This research aims to (1) find out how financial administration is managed in the batik industry in Kampoeng Batik Laweyan, (2) find out the obstacles and constraints in managing financial administration in the batik industry in Kampoeng Batik Laweyan, and (3) find out solutions to the obstacles and obstacles in financial administration management in the batik industry in Kampoeng Batik Laweyan. This research is a qualitative descriptive study. Data sources for this research include informants (batik industry players in Kampoeng Batik Laweyan), and documents (archives and others). The sampling technique was carried out using purposive sampling. Data collection was carried out using interview, observation and documentation techniques. The validity testing technique used is source triangulation and method triangulation. Data analysis using interactive data reduction techniques. The results of this research were as followed. First, financial administration management in the batik industry in Kampoeng Batik Laweyan was good but there needed to be improvement in several aspects so that it could be even better. Financial planning had been implemented quite well, then financial recording had been implemented very well, then reporting had also been implemented well and the control section needed to be improved further so that financial administration became better and more optimal. Second, the obstacles that exist in managing financial administration in the batik industry in Kampoeng Batik Laweyan were the lack or low level of knowledge of the owners or financial administrators of the batik industry regarding financial administration management. Apart from that, there were still some owners or financial managers in the batik industry who had little or no awareness regarding the importance of managing financial administration. Another obstacle was that recording and reporting in financial administration management was recorded conventionally or manually. Third, the solution to overcome the obstacles that occurred in managing financial administration in the batik industry in Kampoeng Batik Laweyan was the relevant agencies or forums could provide training or outreach regarding complete financial administration managemen. Recruiting human resources or employees who were experts in the financial sector could also be a solution to overcome obstacles in managing financial administration.